U.S. Cooperative Extension's response to substance misuse: A scoping review - Hagaman, Angela; Roark, Kristen; Washburn, Lisa Tucker (Frontiers in Public Health, 2023)
Background The U.S. has experienced exponential growth in overdose fatalities over the past four decades and more than 22 million people are currently living with a substance use disorder (SUD). While great strides have been made in advancing the science of SUD prevention and treatment, proven programs and interventions are not commonly disseminated at scale in impacted communities. The U.S. Cooperative Extension System (Extension) has been recognized as a valued partner in addressing SUD in communities. Federal funding supporting Extension's response to the opioid epidemic reached 35 million in 2021 primarily through two grant programs: the United States Department of Agriculture's (USDA) Rural Health and Safety Education program; and the Substance Abuse and Mental Health Services Administration (SAMHSA) Rural Opioid Technical Assistance (ROTA) grants. The primary objective of this scoping review was to identify the range of Extension activities aimed at mediating substance misuse. Methods Authors utilized the PRISMA-SCR model to complete this scoping review. Due to the nature of Extension work and the expectation that few activities would be cited in the peer-reviewed literature, the scoping review included a search of peer-reviewed databases, Extension websites for each state and U.S. territory, and the utilization of a web search engine. Upon initial analysis of records returned, authors noted a discrepancy between results returned and the number of states receiving ROTA grants. Thus, authors supplemented the PRISMA-SCR review protocol with a systematic procedure for investigating ROTA funded activities not readily apparent in the peer-reviewed or grey literature. Results A total of 87 records met inclusion criteria. Findings included seven peer-reviewed articles and 80 results from the grey literature. An additional 11 ROTA grantees responded to requests for information regarding state level activities. Conclusions Nationwide, Extension has scaled multiple efforts to address SUD operating through a loose confederation of organizations connected to the land-grant system. Most activities are funded by federal grants and focus on state-sponsored training and resource sharing. The volume of effort is significant, however, implementation at the community-level has been slow. Significant opportunities exist for local adoption of evidence-based practices aimed at mitigating SUD.